“Autoestima y Migración. Estudio en la Unidad Educativa “Riobamba”. Riobamba. Chimborazo. Perìodo Marzo - Julio 2016”. - Zamora Carangui, Jenny Verónica (2017)
The purpose of this research called "Self-esteem and Migration. Study in the "Unidad Educativa Riobamba". Riobamba. Chimborazo. On March - July 2016," is determine efficiently how parents' migration influences their children's self-esteem, its effects on academic performance. It is essential to know the causes that push to adolescents to have a low self-esteem and assume roles that do not correspond to them, indicating the potentialities and difficulties that have these families and why this makes it difficult for them to fulfill their project of life. For this reason the problem was formulated and solve it through this researching, in which specific objectives were proposed to get them at the end of the researching. Also through the theoretical framework studying two variables and clear them was possible, it allowed us to know more about this topic, a descriptive field research was carried out, doing a survey to the students in ninth year of Basic Education of the "Unidad Educativa Riobamba”. Collecting and adapting to the several specialized authors’ suggestions. Also working directly with those involved, concluding with their tabulation, analysis and interpretation and representing them in statistics graphs. Concluding that those students who come from migrants’ families will have an unfavorable academic performance because the adolescent who does not have one of his parents feels unmotivated towards the responsibilities and school activities that they must fulfill. This is caused by the lack of attention, interest, communication and the short time spent to them by one of their parents, giving as a result your kids develop a low level of self-esteem and at the same time low academic performance.